Early focal electroencephalogram and neuroimaging findings predict epilepsy development after aneurysmal subarachnoid hemorrhage - Campos-Fernández, D; Montes, A; Thonon, V; Sueiras, M; Rodrigo-Gisbert, M; Pasini, F; Quintana, M; López-Maza, S; Fonseca, E; Coscojuela, P; Santafe, M; Sánchez, A; et al. (Epilepsy & behavior, 2024)
•Patients with cortical involvement on brain CT present higher risk of late seizures.•Epileptiform abnormalities are associated with a 6-fold increased risk of epilepsy.•Focal slowing correlates with cortical involvement and higher remote seizure rate.•Early routine EEG and neuroimaging provide potential biomarkers of post-SAH epilepsy. Seizures are a common complication of subarachnoid hemorrhage (SAH) in both acute and late stages: 10–20 % acute symptomatic seizures, 12–25 % epilepsy rate at five years. Our aim was to identify early electroencephalogram (EEG) and computed tomography (CT) findings that could predict long-term epilepsy after SAH. This is a multicenter, retrospective, longitudinal study of adult patients with aneurysmal SAH admitted to two tertiary care hospitals between January 2011 to December 2022. Routine 30-minute EEG recording was performed in all subjects during admission period. Exclusion criteria were the presence of prior structural brain lesions and/or known epilepsy. We documented the presence of SAH-related cortical involvement in brain CT and focal electrographic abnormalities (epileptiform and non-epileptiform). Post-SAH epilepsy was defined as the occurrence of remote unprovoked seizures ≥ 7 days from the bleeding. We included 278 patients with a median follow-up of 2.4 years. The mean age was 57 (+/-12) years, 188 (68 %) were female and 49 (17.6 %) developed epilepsy with a median latency of 174 days (IQR 49–479). Cortical brain lesions were present in 189 (68 %) and focal EEG abnormalities were detected in 158 patients (39 epileptiform discharges, 119 non-epileptiform abnormalities). The median delay to the first EEG recording was 6 days (IQR 2–12). Multiple Cox regression analysis showed higher risk of long-term epilepsy in those patients with CT cortical involvement (HR 2.6 [1.3–5.2], p 0.009), EEG focal non-epileptiform abnormalities (HR 3.7 [1.6–8.2], p 0.002) and epileptiform discharges (HR 6.7 [2.8–15.8], p < 0.001). Concomitant use of anesthetics and/or antiseizure medication during EEG recording had no influence over its predictive capacity. ROC-curve analysis of the model showed good predictive capability at 5 years (AUC 0.80, 95 %CI 0.74–0.87). Focal electrographic abnormalities (both epileptiform and non-epileptiform abnormalities) and cortical involvement in neuroimaging predict the development of long-term epilepsy. In-patient EEG and CT findings could allow an early risk stratification and facilitate a personalized follow-up and management of SAH patients.